Development of Interactive Mathematics Learning Media on Geometry Material - Putra R., Andika; Rahmawati Z., Yulia (S&Co Publishing, 2022)
The purpose of this study was to describe the development of valid, practical, and effective learning media on Geometry materials with worksheets equipment. This research type was development research using the modified Borg & Gall procedures by several main steps, namely product analysis developed, initial product development, and product trials. The product trials carried out consisted of two stages, namely expert validation was carried out to know whether the created learning media was suitable for use or not, from the validation results it was concluded that learning media could be used with slight revisions, then small-scale trials were carried out to find out college student responses to learning media by using college student response questionnaires and conducting tests (evaluations) to obtain media effectiveness data, while the results of the development of interactive mathematics learning media are valid with scores of 3.64 and 3.36, practical with a score of 3.83 and very effective with 90% complete mastery of the material.